THE USE OF EXPRESSIVE SPEECH ACTS IN HANNAH MONTANA SESSION 1 - Nur Vita Handayani (Register Journal, 2015)
This study aims to describe kinds and forms of expressive speech act in Hannah Montana Session 1. It belongs to descriptive qualitative method. The research object was expressive speech act. The data source was utterances which contain expressive speech acts in the film Hannah Montana Session 1. The researcher used observation method and noting technique in collecting the data. In analyzing the data, descriptive qualitative method was used. The research findings show that there are ten kinds of expressive speech act found in Hannah Montana Session 1, namely expressing apology, expressing thanks, expressing sympathy, expressing attitudes, expressing greeting, expressing wishes, expressing joy, expressing pain, expressing likes, and expressing dislikes. The forms of expressive speech act are direct literal expressive speech act, direct non-literal expressive speech act, indirect literal expressive speech act, and indirect non-literal expressive speech act.